Reflectance confocal microscopy of an inverted follicular keratosis mimicking a squamous cell carcinoma - Sarah Hocker; Harold S. Rabinovitz; Margaret Oliveiro; Jane Grant-Kels; Alon Scope (Mattioli1885, 2017)
Distinguishing between benign and malignant neoplasms of the skin is a daily challenge to dermatologists. With the use of a dermatoscope and other imaging devices, the diagnosis is often more precise. The confocal microscope is a device that uses a near-infrared laser to perform noninvasive imaging of the skin. The benefit is that the images immediately provide additional, cellular-level information that can assist in diagnosis. However, lesions may share overlapping characteristics on confocal microscopy, and hence, benign lesions can still display confocal features concerning for a cancerous process, justifying a biopsy. Here, we present a case of an inverted follicular keratosis imitating a squamous cell carcinoma on confocal microscopy.